2019
DOI: 10.18632/oncotarget.26884
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-O-GlcNAcylation promotes epithelial-mesenchymal transition in endometrial cancer cells

Abstract: Diabetic women have a 2–3 fold increased risk of developing endometrial cancer, however, the molecular aspects of this risk are not fully understood. This study investigated the alteration of cellular O-GlcNAcylation of proteins as the potential mechanistic connection between these two conditions. The endometrial cancer cell line (Ishikawa) was utilized to study the effect of dysregulation of O-GlcNAcylation on epithelial mesenchymal transition (EMT). Hyper-O-GlcNAcylation (via 1 μM Thiamet-G/ThmG or 25 mM Glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Conversely, GCs of large follicles are presumably nearing the stages of terminal differentiation or luteinization, wherein cell division is less frequent [ 29 , 30 ], acquisition of LH receptors occurs [ 31–33 ], and resistance to apoptosis becomes attainable [ 34 ]. Indeed, under culture conditions, we and others have found that GCs typically obtained from small antral follicles exhibit greater rates of proliferation, with a shorter generation interval, and are less prone to spontaneous luteinization than GCs obtained from larger follicles [ 20 , 35 , 36 , unpublished observations and supplementary information]. In the current study, GC proliferation was measured by both mitochondrial activity (MTS assay) and the cell proliferation marker, Ki-67 (immunodetection), which is only expressed by dividing cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Conversely, GCs of large follicles are presumably nearing the stages of terminal differentiation or luteinization, wherein cell division is less frequent [ 29 , 30 ], acquisition of LH receptors occurs [ 31–33 ], and resistance to apoptosis becomes attainable [ 34 ]. Indeed, under culture conditions, we and others have found that GCs typically obtained from small antral follicles exhibit greater rates of proliferation, with a shorter generation interval, and are less prone to spontaneous luteinization than GCs obtained from larger follicles [ 20 , 35 , 36 , unpublished observations and supplementary information]. In the current study, GC proliferation was measured by both mitochondrial activity (MTS assay) and the cell proliferation marker, Ki-67 (immunodetection), which is only expressed by dividing cells.…”
Section: Discussionmentioning
confidence: 98%
“…Enhancement of O-GlcNAcylation, or hyper-O-GlcNAcylation, is associated with increased cell proliferation and amplified tumorigenic potential [ 36 , 37 ]. Specifically, hyper-O-GlcNAcylation enhances cancer cell aggressiveness through increased expression of epithelial-mesenchymal transition genes, stimulating cell proliferation, and enhancing cell migration and/or invasiveness [ 36 ]. In contrast, a diminishment of O-GlcNAcylation, or hypo-O-GlcNAcylation, impairs these measures [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AHNAK has not been previously associated with neuroblastoma, but has been implicated in several cellular functions associated with cancer, including being listed one of six putative cancer genes involved in the evolution of nine cancer types across 3000 cancer genomes [59]. Most interestingly, AHNAK has been reported to be associated with enhanced proliferation and migration in rhabdomyosarcoma [60] among other cancers as well as supporting EMT in hepatoblastoma [61], endometrial [62] and lung [63] cancer cells as well as pancreatic ductal adenocarcinoma [42] and gastric cancer [64]. A similar role in neuroblastoma would be well in line with our previous observations that several signaling elements involved in EMT regulation are mutated in relapsed neuroblastomas [13].…”
Section: Discussionmentioning
confidence: 99%
“…For example, OGT is required for the induction and maintenance of EMT in NSCLC (84). In addition, hyper-O-GlcNAcylation contributes to the EMT of EC (85). The cell surface protein E-cadherin mediates cell-cell interactions, which is directly correlated with cancer cell adhesiveness, and this therefore mediates the invasive and metastatic capabilities of cells (86).…”
Section: O-glcnacylation Of E-cadherin In Cancer Metastasismentioning
confidence: 99%